2016
DOI: 10.1097/qai.0000000000000905
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional and Immunological Correlates of Memory and Neurocognitive Development Among HIV-Infected Children Living in Kayunga, Uganda

Abstract: Objective To identify the nutritional and immunological correlates of memory and neurocognitive development as measured by the Mullen Scales of Early Learning (MSEL) and by the Color Object Association Test (COAT) among children in Uganda. Design This analysis uses baseline data collected between 2008 and 2010 from 119 HIV-infected children ages 1–6 years participating in a randomized controlled trial of an interventional parenting program in Kayunga, Uganda. Methods Peripheral blood draws were performed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…For example, decreased brain-derived neurotrophic factor (BDNF) production has been found in the brains of the CD4-depleted mice (Wolf et al, 2009). However, the current results are in line with previous human studies, for example in children with HIV infection (Ruisenor-Escudero et al, 2016). Also, in a study in healthy aging, better performance in memory and executive function were found for those with lower bloodderived CD4 T-cell counts and higher B-cell counts (Serre-Miranda et al, 2015).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…For example, decreased brain-derived neurotrophic factor (BDNF) production has been found in the brains of the CD4-depleted mice (Wolf et al, 2009). However, the current results are in line with previous human studies, for example in children with HIV infection (Ruisenor-Escudero et al, 2016). Also, in a study in healthy aging, better performance in memory and executive function were found for those with lower bloodderived CD4 T-cell counts and higher B-cell counts (Serre-Miranda et al, 2015).…”
Section: Discussionsupporting
confidence: 90%
“…Three levels of memory recall were evaluated, including immediate, short-and long delay memory recall. In particular, given Given findings from Ruisenor-Escudero et al (2016) and Kusdra et al (2000) we expected an inverse associations between memory recall and both CD4 + and CD8+. Given those of Grassi-Oliveira et al (2011), we anticipated an inverse association between memory recall and IL-6.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Disability is also likely to be associated with HIV infection in children as it had statistically significant odds ratios in the univariate model and the multivariate model that excluded mother’s HIV status. Neurocognitive impairment, developmental delays, and motor abnormalities such as spasticity have been observed among pediatric HIV patients, and may account for the high HIV prevalence among children with disability and likely association between disability and HIV infection in our study [35, 36]. Being malnourished likely reflects severe HIV disease and has been associated with disease progression and mortality in children [37].…”
Section: Discussionmentioning
confidence: 96%
“…We found a positive association between child HAZ and all MSEL sub-scales, including the Mullen Composite score. Previous studies from Uganda [40] and Tanzania [41] have found that wasting and stunting were independently associated with poorer psychomotor and neurodevelopmental outcomes. Given Uganda’s high prevalence of child undernutrition (estimated at 35% among children younger than 5 years) [42] and the high vulnerability to poor neurodevelopmental outcomes of undernourished infants affected by HIV, wasting and stunting should be considered as markers of children who might benefit from early neurodevelopment interventions coupled with nutritional support.…”
Section: Discussionmentioning
confidence: 99%